Micromorphologic Analysis of the Dentine Etching Human Being for Primer Acidulous Varying Preparation Technique: Diamond Tip, Drill Carbide and CvDentus Tips - Manon Eleonora de Ladalardo MARTINS; Mirian Rubio FARIA; Maurício Rufaiel MATSON (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2006)
Objective: The proposal at this work is to evaluate, the standard of etching of the dentine after the application of acidulous primer of a self etching adhesive system (Clearfill Liner Bond 2) using SEM. Method: Preparations cavities were done on 5 human molars, as follows: For each tooth, 2 preparations with diamond tip , 2 with drills carbide in low rotation and 2 with CVDentus tip were done; they received a type of treatment: without acid etching, acid etching with acid phosphoric 37% for 15s and application of acidulous primer. The specimens had been analyzed in SEM, where images were enlarged to 200, 2000 and 5000 times. Results: In the cases prepared with CVDentus tip, the smear layer with appearance of flakes, was noticed; in addition to that we also noticed the presence of exposed dentin tubules. On the preparation with diamont tip conventional and drill carbide the smear layer presented a more compacted form. For the cases that CVDentus tip were used, a smear layer with flake aspect was present besides the presence of displayed dentin tubules. In the conventional preparations (diamont tip) smear layer presented residues in dentine intertubular. Conclusion: For this analysis we can affirm that with the use of the CVDentus tip and the application of primer acidulous we have the smear layer less adhered, with a standard of different etching.